The Effect of COVID-19 Pandemic on Accounting Classrooms, South Africa (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
Traditionally, teaching and learning processes have always taken place in classroom environment that promote effective teaching and learning be it using the contact or virtual platform, however, the Corona Virus Disease -19 called COVID-19 has disrupted these educational processes. Overall, in research the impact of COVID-19 on the education system has gained critical importance, with the hope of drawing scientific driven solution to this predicament. Subsequently, in attempt to contribute some insights on dilemma facing teaching and learning in schools during COVID -19, this study is premised on the belief that, although effect of the pandemic is broad a unit level analysis of the educational processes and context specific driven approach should be adopted towards understanding the impacts of the pandemic. As a result, this study thus investigated the impact of COVID-19 in accounting classrooms in selected South African high schools in rural based contexts of Amatole. A qualitative approach in particular a case study research design was employed. The findings revealed that, preparation of accounting learners was negatively affected especially those who were in the exit level, as a result these learners are likely to struggle to cope with accounting studies in their first year at university or college due to challenges of COVID-19. Findings further revealed that both teachers and learners were not given any form of support during the lock down due to COVID-19 pandemic. There researchers recommend that counseling workshop is for learners should be conducted to alleviate the pressure associated with COVID-19 pandemic.